(untitled) (Applied Biological Research, 2023)
Wrightia tinctoria has long been exploited for its therapeutic potential and has proved an effective natural medicine for various disorders and illnesses. This study was aimed to assess the phytochemical and biological activity of W. tinctoria extracts that would support both the traditional and pharmaceutical uses of its leaves. Following the consecutive extractions of fresh W. tinctoria leaves using petroleum ether, chloroform, methanol, and aqueous solvents in sequence; several phytochemicals were discovered. The study revealed the presence of alkaloids, flavonoids, tannins, beta-cyanin, fats and fixed oil in the extracts. The antioxidant activity of extracts using DPPH (2,2-diphenylpicryl hydrazyl) assay, antibacterial activity (disc diffusion assay), and the extract’s apoptotic character (acridine orange and ethidium bromide staining) were also assessed. The study revealed relatively high bioactivity in chloroform extract. The chloroform extract showed good antioxidant (IC50 296 µg mL-1), anti bacterial and anticancer (100 µg mL-1) activity in SKBr3 cell lines. It was purified using column chromatography. The prominent fraction was chosen and characterized by GCMS analysis. Many active biomolecules with significant biological activity were found. Further studies are needed to understand the mechanism of action of these potent compounds noticed in W. tinctoria extract.